On the contribution to the alignment during an organizational change: Measurement of job satisfaction with working conditions - Wafa Boulagouas; Susana García-Herrero; Rachid Chaib; SixtoHerrera García; Mébarek Djebabra (Journal of safety research, 2021)
Introduction: Modern approaches to Occupational Health and Safety have acknowledged the important contribution that continuous improvements to working conditions can make to the motivation of employees, their subsequent performance, and therefore to the competitiveness of the company. Despite this fact, organizational change initiatives represent a path less traveled by employees. Specialized literature has drawn on the fact that employees’ satisfaction presents both the foundation and catalyst for effective implementation of improvements to working conditions. Method: This paper conceptualizes the alignment of employees through measurement of job satisfaction and uses the Bayesian Network to assess the influence of human factors, particularly the cognitive, emotional, and behavioral aspects. Toward this aim, the Bayesian Network is evaluated through a cross-validation process, and a sensitivity analysis is then conducted for each influential dimension: emotional, cognitive, and behavioral. Results: The results reveal that these three dimensions are interrelated and have a direct influence on job satisfaction and employees’ alignment during the organization change. Further, they suggest that the best strategy for enhanced alignment and smooth conduct of organizational changes is simultaneous enhancement of the three dimensions. Practical applications: This study shows the influence of emotional, cognitive, and behavioral dimensions on job satisfaction and employees’ alignment during the organizational change. Furthermore, it elaborates the way to develop efficient and effective strategies for a successful change implementation and sustained alignment.

An investigation into unsafe behaviors and traffic accidents involving unlicensed drivers: a perspective for alignment measurement - Wafa Boulagouas; Susana García-Herrero; Rachid Chaib; Juan Diego Febres; Miguel Ángel Mariscal; Mébarek Djebabra (International Journal of Environmental Research and Public HealthInternational Journal of Environmental Research and Public Health, 2020)